MENEGOSIASIKAN KEBERAGAMAN DAN MEMBANGUN IDENTITAS BERSAMA MELALUI MODERASI BERAGAMA DI KOMUNITAS TRANSMIGRAN - Andi Tenri Leleang; Ahmad Khidir Al Ikhlas; Ambo Ahsan bin Embok Raub (IAI DDI Mangkoso, 2026)
This study aims to analyze the dynamics of multicultural harmony within the transmigrant community and the practice of religious moderation in Toabo Village. Toabo Village is known as “Mini Indonesia” because of the diversity of its community. Despite this diversity, the transmigrant community in Toabo is able to live peacefully and harmoniously through the practice of religious moderation. This study employs a qualitative approach using a case study method. Data were obtained through interviews with community members, religious leaders, and community leaders, as well as through observation and documentation. The data were analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings show that multicultural harmony in Toabo Village is manifested through mutual respect in religious practices, cross-religious participation in religious celebrations, the involvement of various groups in cultural festivals, and adjustments in social activities to respect the religious needs of each group. Harmony is also supported by the roles of religious and community leaders in resolving differences through deliberation and by continuous social interaction. On the other hand, technological development and social media pose challenges because they can introduce provocative religious narratives from outside the local community. This study shows that religious moderation within a transmigrant community is manifested not only through tolerance but also through social practices, cross-group cooperation, and the community’s ability to manage differences